PERSONAL DOSE DATABASE SOFTWARE FOR EXTERNAL EXPOSURE - Chevy Cahyana (Buletin Limbah, 2005)
PERSONAL DOSE DATABASE SOFTWARE FOR EXTERNAL EXPOSURE. The ERDBase software for external radiation dose database has been made using Borland Delphi 5.0 programming language. The software is proven to be efficient in utilizing memory. It has been tested for workers in the Safety and Environment Division of the Radioactive Waste Management Development Center. Using this software, one can save a large memory and increase service quality in personal dose management.